Early Referral to an ALS Center Reduces Several Months the Diagnostic Delay: A Multicenter-Based Study - Martínez-Molina, Marina; Argente-Escrig, Herminia; Polo, Margarita F.; Hervás, David; Frasquet, Marina; Cortés, Victoria; Sevilla, Teresa; Vázquez-Costa, Juan F. (Frontiers in Neurology, 2020)
Objective To analyse those factors contributing to the diagnostic delay in ALS. Methods Consecutive ALS patients were categorized as those studied in departmental hospitals and those studied in a referral ALS center. Demographic and clinical variables, together with data of the diagnostic pathway were collected. Multivariable models were used to assess their effect in the time between symptoms onset and the first neurologist visit (time symptoms-neurologist), in the time between the first neurologist visit and the diagnosis (time neurologist-diagnosis) and in the diagnostic delay. Results 166 ALS patients with a median diagnostic delay of 11.53 months (IQR: 6.68, 15.23) were included. The median diagnostic delay was 8.57 (5.16, 11.61) in the referral center and 12.08 (6.87, 16.8) in departmental centers. Bulbar onset, fast progression rate, upper motor neuron predominant phenotype and an early referral to the neurologist associated to shorter time symptoms-neurologist. Being studied in a referral center associated to shorter time neurologist-diagnosis. Comorbidities, familial ALS, bulbar onset, early referral to the neurologist and being studied in a referral center were related to shorter diagnostic delay. For patients studied in departmental hospitals, fast progression rate was also strongly associated to shorter time neurologist-diagnosis and diagnostic delay. Conclusion Unmodifiable factors (comorbidities, familial ALS, bulbar onset and progression rate) as well as modifiable factors (early referral to the neurologist and the evaluation in an ALS referral center) have an independent effect in the diagnostic delay. The universalization of ALS Units is probably the most efficient measure to reduce the diagnostic delay.